Studi Perilaku Mahasiswa Arsitektur Terhadap Kantin Jurusan Teknik Arsitektur Fakultas Teknik Universitas Lambung Mangkurat - Laila Zohrah; Rudi Hartono (INFO-TEKNIK, 2005)
This research study the relationship between behaviour and (canteen) environment, especially correlation between behaviour which have been found with the context of studied. And only behaviour which dealt with architectural problem will be selected, and then solved. And in this hand out also studied the dominant environment influence by physical elements that caused certain behavioural appearance (specially the negative behaviour).In architecture study of behavioural and environmental, according to Haryadi and Setiawan in its book Arsitektur Lingkungan dan Perilaku (1996: 17) mentioned that personal dimension divided into two matters, physical factor and psychological factor which is in relation context between behaviour and its environment, both will influence the individual response to the occurrence stimuli environment.From that statement, we can be said that reaction of human through his motion and or its behaviour is depending from the setting whereabouts he reside concerning both psychological and physical aspect, and also his/her culture background and ability of to understanding the meaning of technological, economics and political system will also give the influence to human behaviour.Through the method of behavioural approach and mapping, canteen as object for this research showing us that canteen which in function build as place to rest, in the reality also own the prerequisite that having a very big effect to behavioural pattern of people around its. In example, canteen air circulation, wide, lighting, etc.